Subject Heading: Its application for consistent and uniform subject entries for Literature - ARYAL, BISHNU (TULSSAA Journal, 2025)
This article states the concept of Subject headings and its current situation. Catalogue is defined; catalogue codes and their history are also stated, which gives brief history of cataloguing and its rules. Subject related subjects are also described. The main focus of the study is stated as the Nepali subject headings and its application in Nepali libraries.TULSSAA Vol.4(3) 2006 pp.4-6